'Asianizing the field': questioning Critical Tourism Studies in Asia. Issue 4 (1st July 2021) - Chang, T. C.
Abstract: The relationship between Critical Tourism Studies (CTS) and Asian tourism research is worthy of research. In particular, the challenges that CTS offers to Asian tourism scholarship and how the latter expands the scope of critical thought are areas for consideration. CTS deconstructs mainstream concepts and theorizations and gives voice to the marginalized in the real world of tourism industry and also in the research domain of knowledge creation. How CTS and Asian tourism scholarship are mutually implicated is considered through six exploratory questions relating to principle, language, authorship, concepts, emancipation and pedagogy. Drawing on select literature in Asia, the criticality of extant studies is examined and meaningful directions for further critical scholarship charted. The ultimate goal is to work towards a Critical Asian Tourism Studies (CATS) in which the mutually reinforcing relationship between Asian tourism scholarship and CTS is celebrated, and where research on Asian tourism can be made more theoretical, inclusive and emancipative.